The LIBER GdC map library usage survey, Summer 2003 - Millea, N (2004)
This paper represents an analysis of map library usage across Europe in 2002/03, and an attempt to identify significant trends. Proposals are suggested to both address and exploit the behavioural patterns revealed in responses gathered from map users across the continent.